Psychometric Evaluation of the EQ-5D-5L in Indonesia Patients with Type 2 Diabetes Mellitus - Setiyaningrum, Annisa; Solikhah, Solikhah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Diabetes is a chronic disease affecting a significant portion of Indonesians populations with a substantial impact on the quality of life. Despite its widespread usage, the EQ-5D-5L remains a generic measure that may fail to capture condition-specific characteristics such as self-care obstacles, social support, psychological burdens, and complications in patients with type 2 diabetes mellitus. These constraints emphasize the theoretical gap and the need for a personalized remedy. Methods: This study used a cross-sectional approach and was conducted at six community health centers (Puskesmas) in Yogyakarta City between October 2024 and February 2025. A total of 400 respondents aged 19-59 years who consented to participate were included in the study. Content validity testing was conducted by expert panel, who provided feedbacks on the relevance of the items, revisions prior to pilot testing of the instrument. Face validity was evaluated with 40 respondents. Model fit and construct validity were analyzed using Confirmatory Factor Analysis (CFA). Results: The Cronbach’s Alpha value for internal concistency reliability was 0.86. The majority of respondents were female (64.75%), had a moderate level of education (67.50%), and belonged to the low income bracket (61.75%). Hypertension was the most commonly reported complication (26.75%). Respondents’ quality of life was categorized as fairly good. Confirmatory factor analysis (CFA) revealed that the social support dimension did not meet the validity threshold. After its removal, the five dimensional model—mobility, self-care, usual activities, pain/discomfort, and anxiety/depression showed satisfactory construct validity and reliability, with standardized loadings ranging. The Comparative Fit Index (CFI) was 0.923, while the Tucker-Lewis Index reached 0.885, RMSEA (0.125), and SRMR (0.069) suggesting a model fit that approaches, but does not fully meet, ideal thresholds. Conclusion: The instrument exhibits acceptable reliability and preliminary validity consistent with the theoretical construct. However, revision of the social support items and further validation in broader populations are necessary before wider application.